THE EFFECT OF INTERNAL BUSINESS COMMUNICATION ON THE CORPORATE IMAGE - Anamaria-Mirabela POP; Monica-Ariana SIM (Annals of the University of Oradea: Economic Science)
Since it is one of the most fundamental elements of establishing a relationship, effective communication is necessary in almost all professions. Business thrives on communication since it depends so heavily on relationships between diverse people. Any type of communication is always important to business. It increases a company's efficacy and efficiency and keeps the appropriate ratio of different strategies for projecting the ideal image. The two types of communication in business are internal and external. Communication between two organizations, as well as between a company and its clients, is referred to as external communication. Information exchange within a company is referred to as internal communication. It happens amongst co-workers as well as between employers and employees. Internal communication is therefore essential for connecting with employees, running the business, and improving the company's reputation. No matter how big or how profitable a business is, internal communication is crucial. It significantly affects an organisation's success, since effectively articulated strategies help enhance employee productivity, employee engagement and team collaboration. The open and transparent environment created by the communication process helps employees comprehend the company's objective and their individual role in achieving it. It guarantees excellent employee cooperation in achieving the shared objective. Good internal communication promotes exceptional staff engagement, which in turn increases corporate performance and ensures high levels of customer satisfaction. Internal corporate communication is essential for impacting daily operations, fostering cross-departmental relationships, and, most significantly, dismantling organizational silos. It aids in creating a united culture throughout the company to enable all employees to make the best judgments. Consequently, internal communication has an impact on a company's productivity, profitability, and overall brand image. It also influences both bosses and employees' morale. Thus, one must create a successful internal company communication plan to engage the workforce for greater production and pay attention to their worries and anxieties over their jobs. Therefore, the paper's main goal is to analyze internal communication tasks while concentrating on how they affect various areas of business performance. The paper is based on a critical analysis of the relevant literature, taking into account works that address the problem's practical aspect.